THE EFFECTIVENESS OF USING TEAMS GAMES TOURNAMENTS (TGT) IN TEACHING READING OF NARRATIVE AT SECOND GRADE OF MA MAMBAUS SHOLIHIN - Zumrotul Faricha; Khoiruh Huda (FKDP (Forum Komunikasi Dosen Peneliti), 2019)
The objective of the research was to see the effectiveness Teams Games Tournaments (TGT) technique in teaching reading of the narrative text at the second Grade students of MA Mambaus Solihin and also to help the English teachers create interactive activities for students while learning reading of a narrative text. The method applied in this research was pre-experimental research. There was class, this research was conducted through the following procedures: giving the pre-test, and giving a post-test. The result of the research proved that the Teams Games Tournaments (TGT) technique is effective to be used in learning reading of a narrative text. The finding showed that both groups had a significant difference. It could be said that the pre-test and post-test value is increased. it was proven from the materials, scores and activities which were used in the C class that support students’ interesting to learn more about reading topic.